Maternally sequestered therapeutic polypeptides – a new approach for the management of preeclampsia - Bidwell, Gene L.; George, Eric M. (Frontiers in Pharmacology, 2014)
The last several decades have seen intensive research into the molecular mechanisms underlying the symptoms of preeclampsia. While the underlying cause of preeclampsia is believed to be defective placental development and resulting placental ischemia, it is only recently that the links between the ischemic placenta and maternal symptomatic manifestation have been elucidated. Several different pathways have been implicated in the development of the disorder; most notably production of the anti-angiogenic protein sFlt-1, induction of auto-immunity and inflammation, and production of reactive oxygen species. While the molecular mechanisms are becoming clearer, translating that knowledge into effective therapeutics has proven elusive. Here we describe a number of peptide based therapies we have developed to target theses pathways, and which are currently being tested in preclinical models. These therapeutics are based on a synthetic polymeric carrier elastin-like polypeptide (ELP), which can be synthesized in various sequences and sizes to stabilize the therapeutic peptide and avoid crossing the placental interface. This prevents fetal exposure and potential developmental effects. The therapeutics designed will target known pathogenic pathways, and the ELP carrier could prove to be a versatile delivery system for administration of a variety of therapeutics during pregnancy.